Application of artificial intelligence to measure attention levels in university students - Edquén Barboza, Wilmer Alexander; Carlos Flores Ramirez, Roberto; Luna Villanueva, Jhon Marcos; Ramirez Pezo, Yngue Elizabeth; Lévano, Danny; Casildo-Bedón, Nancy Esther (Frontiers in Education, 2026)
ObjectiveTo evaluate the effect of an AI-assisted attentional monitoring system on the perception of class dynamism and the self-assessment of attention among university students.MethodsA quasi-experimental design was employed with 160 students divided into an experimental group, which attended classes with attentional monitoring and real-time feedback provided to the teacher, and a control group, which received traditional instruction. Perception of attention and dynamism was assessed pre- and post-intervention using the AIDA questionnaire.ResultsThe experimental group exhibited significant increases in perceived class dynamism and attentional self-regulation compared to the control group (p < 0.05), demonstrating improved engagement during the session.ConclusionAI-assisted immediate feedback was associated with enhanced attention and student participation, highlighting the potential of such tools to support and strengthen teaching dynamics in in-person educational settings.